2015
DOI: 10.1093/oep/gpv032
|View full text |Cite
|
Sign up to set email alerts
|

Information technologies and subjective well-being: does the Internet raise material aspirations?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 43 publications
(44 reference statements)
1
48
0
1
Order By: Relevance
“…This is very likely the case with the internet. Clark and Senik () show that those who have internet access at home are also more likely to report that they compare their income to others (although they do not have data on exogenous changes in internet access, for which see Lohmann, ). Over the course of economic growth, this dampening effect will be concentrated amongst the richer, and perhaps also amongst those who were previously among the happiest.…”
Section: Discussionmentioning
confidence: 99%
“…This is very likely the case with the internet. Clark and Senik () show that those who have internet access at home are also more likely to report that they compare their income to others (although they do not have data on exogenous changes in internet access, for which see Lohmann, ). Over the course of economic growth, this dampening effect will be concentrated amongst the richer, and perhaps also amongst those who were previously among the happiest.…”
Section: Discussionmentioning
confidence: 99%
“…Socio-economic inequality can manifest into many issues, such as lack of opportunity and a decrease in the subjective well-being of individuals [16]. Income inequality rose sharply in the United States (US) in the last forty years, but has increased only slightly in other countries such as France and Japan [15].…”
Section: Income Inequalitymentioning
confidence: 99%
“…To estimate the effects of Internet access on life satisfaction, a standard model of the determinants of life satisfaction is used (Frey and Stutzer, 2005;Helliwell, 2008;Dolan, Peasgood and White, 2008), where Internet access is used as the explanatory variable of interest alongside a set of demographic characteristics as well as country-fixed effects to control for country-level variance in terms of living standards as well as potential cultural determinants of life satisfaction responses . This approach does not differ substantially from other studies into the relationship between life satisfaction and Internet access or use (Graham and Nikolova, 2012;Lohmann, 2015). Conceptually, the nature of the life satisfaction variable lends itself best to an ordered probit model.…”
Section: Annex 2a Internet Access and Life Satisfactionmentioning
confidence: 98%
“…The idea that online exposure to political debates increases political engagement finds support in studies that have found positive associations between the online exposure to political discussions and offline political participation (Gil de Zúñiga, Molyneux and Zheng, 2014). The Internet also allows people to exert pressure on political processes through online petition platforms such as Change.org 12 or Avaaz 13 as well as through government-backed political participation platforms such as DemocracyOS 14 in Argentina (Mancini, 2015). Conversely, it has also been suggested that online political engagement may crowd out traditional forms of political participation (Christensen, 2011).…”
Section: Increased Engagement Of Citizens In Civic and Political Commmentioning
confidence: 99%
See 1 more Smart Citation